2016
DOI: 10.1016/j.cub.2016.08.064
|View full text |Cite
|
Sign up to set email alerts
|

Cross-modal impacts of anthropogenic noise on information use

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms The adaptive, stronger response exhibited towards predator faeces compared to control faeces in ambient-noise conditions was detrimentally affected by road-noise playback. Specifically, having taken longer to detect the faeces, the mongooses interacted less with the predator cue, did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 10 publications
1
54
0
Order By: Relevance
“…Greater reliance on visual vs acoustic cues in conditions of increased noise represents an example of cross-modal perceptual weighting (Halfwerk and Slabbekoorn, 2015;Gomes et al, 2016); anthropogenic noise may also cause cross-modal interference (Halfwerk and Slabbekoorn, 2015;Morris-Drake et al, 2016). Increased vigilance likely means greater acquisition of accurate personal information about the current situation; social information, such as that arising from heterospecific alarm calls, can be irrelevant, unreliable or outdated (Giraldeau et al, 2002;Dall et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Greater reliance on visual vs acoustic cues in conditions of increased noise represents an example of cross-modal perceptual weighting (Halfwerk and Slabbekoorn, 2015;Gomes et al, 2016); anthropogenic noise may also cause cross-modal interference (Halfwerk and Slabbekoorn, 2015;Morris-Drake et al, 2016). Increased vigilance likely means greater acquisition of accurate personal information about the current situation; social information, such as that arising from heterospecific alarm calls, can be irrelevant, unreliable or outdated (Giraldeau et al, 2002;Dall et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Previous experimental work has demonstrated that anthropogenic noise can disrupt dwarf mongoose use of information about predation risk, including that provided by the surveillance calls of conspecific sentinels Morris-Drake et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent playback study of road noise, dwarf mongoose ( Helogale parvula ) took longer to detect the presence of predators in noise treatments compared to ambient treatments (Morris‐Drake et al. ).…”
Section: Cross‐modal Interferencementioning
confidence: 99%
“…Noise could distract receivers and so compromise responses to other sensory input (Chan & Blumstein, ; Chan et al, ). For instance, road‐noise playback disrupted the adaptive responses of dwarf mongooses to predator faeces; since there was no auditory element to the predator cue, this cross‐modal effect of noise implies distraction (Morris‐Drake, Kern, & Radford, ). Similarly, fathead minnows ( Pimephales promelas ) subjected to motorboat noise failed to respond to conspecific chemical alarm cues (Hasan, Crane, Ferrari, & Chivers, ), and crabs distracted by boat noise responded with a greater delay to a silent looming object (Chan et al, ).…”
Section: Introductionmentioning
confidence: 99%